Electrocardiographic Strain Pattern Is Associated With Left Ventricular Concentric Remodeling, Scar, and Mortality Over 10 Years: The Multi‐Ethnic Study of Atherosclerosis. Issue 9 (20th September 2017) - Inoue, Yuko Y.; Soliman, Elsayed Z.; Yoneyama, Kihei; Ambale‐Venkatesh, Bharath; Wu, Colin O.; Sparapani, Rodney; Bluemke, David A.; Lima, João A.C.; Ashikaga, Hiroshi
Abstract : Background: Both ECG strain pattern and QRS measured left ventricular (LV) hypertrophy criteria are associated with LV hypertrophy and have been used for risk stratification. However, the independent predictive value of ECG strain in apparently healthy individuals in predicting mortality and adverse cardiovascular events is unclear. Methods and Results: MESA (Multi‐Ethnic Study of Atherosclerosis) is a multicenter, prospective cohort of 6441 participants (mean age, 62 years; 54% women). In 2847 of these participants, cardiac magnetic resonance imaging was repeated ≈10 years later (Year‐10). At Year‐10, 1759 participants underwent cardiac magnetic resonance imaging with gadolinium to detect myocardial scar. During a median follow‐up of 11.7 years, ECG strain (n=168, 2.6%) was significantly associated with all‐cause death (adjusted hazard ratio, 1.33; 95% confidence interval, 1.01–1.77; P =0.045), heart failure (2.62; 1.73–3.97; P <0.001), myocardial infarction (1.86; 1.09–3.18; P =0.024), and incident cardiovascular disease (1.45; 1.06–2.00; P =0.022). ECG strain was also associated with an increase in LV mass (β=9.29 g; P <0.001) and LV mass‐to‐volume ratio (β=0.07 g/mL; P =0.007) and a decline in LV ejection fraction (β=−3.30%; P <0.001). Moreover, ECG strain either at baseline and Year‐10 was associated with LV scar (odds ratio, 4.93 and 5.22; P =0.002 and <0.001, respectively), whereas these associations were not observed in ECG LV hypertrophy. Conclusions: ECG strain is independently associated with all‐cause mortality, adverse cardiovascular events, development of LV concentric remodeling and systolic dysfunction, and myocardial scar over 10 years in multiethnic participants without past cardiovascular disease. ECG strain may be an early marker of LV structural remodeling that contributes to development of adverse cardiovascular events. Clinical Trial Registration: URL:https://www.clinicaltrials.gov/ . Unique identifier: NCT00005487.